A robust dual interval type-2 fuzzy lead–lag based UPFC for stability enhancement using Harris Hawks Optimization - Paital S.R.; Ray P.K.; Mohanty S.R. (My University, 2025)
A Harris Hawks Optimization (HHO)tuned dual interval type-2 fuzzy lead–lag (Dual-IT2FLL) based unified power flow controller (UPFC) is proposed to minimize oscillations in single and multimachine power systems. The proposed damping controller coordinates between the modulation index (MI) and phase angle of series and shunt converters of UPFC simultaneously and is designed using speed deviation, a remote input signal for stability improvement. The performance of the proposed controller is verified through nonlinear time and frequency domain simulations under different operating conditions. The graphical simulations and validations using OPAL-RT OP5600 are presented to access the stability performance. Comparison based on different performance indices (PIs), like mean, standard deviation, overshoots and settling time are also considered to prove the better performance of the proposed HHO tuned dual-IT2FLL based UPFC over others under different operating conditions. © 2021 ISA